Features of lithological and granulometric composition of bottom sediments in the northern part of Laptev Sea - Perevertaylo (Perevertailo), Tatyana Gennadievna; Nedolivko, Nataliya Mikhailovna; Kazhumukhanova, M. (IOP Publishing, 2016)
Bed-sediment samples were collected from the northern part of the Laptev Sea to assess particle-size distribution, mineralogical composition as well as to examine organic matter content. The organic carbon distribution map is constructed to reveal the trends of Corg content and distribution in the surface of the bottom sediments.
Keywords: литологический состав; гранулометрический состав; донные отложения; море Лаптевых; минералогический состав; органические вещества; углерод